Manajemen Strategi Pemberdayaan Mahasiswa Program 1 Rumah Dhuafa 1 Sarjana dalam Meningkatkan Pendidikan di Kota Bekasi - Ananta, Rendra Samba; Sadiah, Dewi (Tadbir: Jurnal Manajemen Dakwah, 2021)
The purpose of this study is to determine strategic management which consists of strategy formulation, strategy implementation, strategy evaluation in empowering students of the 1 Rumah Dhuafa 1 Bachelor program. The method used in this study is a descriptive method with a qualitative approach. The results of this study indicate that the management strategy contained in the empowerment of students of the 1 Rumah Dhuafa 1 Bachelor program consists of three processes, namely strategy formulation in the form of developing a vision and mission accompanied by environmental analysis both internally and externally, goals and objectives, strategies and policy determination. Furthermore, implementing the strategy in the form of programs with the assistance of budgets and several procedures for the implementation. Strategy evaluation, there are semester and yearly evaluations as a form of evaluation and improvement. These three processes in implementing the strategic management process have been running successfully.